Dynamic Hydrogen Production from Methanol/Water Photo-Splitting Using Core@Shell-Structured CuS@TiO2 Catalyst Wrapped by High Concentrated TiO2 Particles - Younghwan Im; Sora Kang; Kang Min Kim; Taeil Ju; Gi Bo Han; No-Kuk Park; Tae Jin Lee; Misook Kang (International Journal of Photoenergy)
This study focused on the dynamic hydrogen production ability of a core@shell-structured CuS@TiO2 photocatalyst coated with a high concentration of TiO2 particles. The rectangular-shaped CuS particles, 100 nm in length and 60 nm in width, were surrounded by a high concentration of anatase TiO2 particles (>4~5 mol). The synthesized core@shell-structured CuS@TiO2 particles absorbed a long wavelength (a short band gap) above 700 nm compared to that pure TiO2, which at approximately 300 nm, leading to easier electronic transitions, even at low energy. Hydrogen evolution from methanol/water photo-splitting over the core@shell-structured CuS@TiO2 photocatalyst increased approximately 10-fold compared to that over pure CuS. In particular, 1.9 mmol of hydrogen gas was produced after 10 hours when 0.5 g of 1CuS@4TiO2 was used at pH = 7. This level of production was increased to more than 4-fold at higher pH. Cyclic voltammetry and UV-visible absorption spectroscopy confirmed that the CuS in CuS@TiO2 strongly withdraws the excited electrons from the valence band in TiO2 because of the higher reduction potential than TiO2, resulting in a slower recombination rate between the electrons and holes and higher photoactivity.